2016
DOI: 10.1371/journal.pone.0147821
|View full text |Cite
|
Sign up to set email alerts
|

Cost-Effectiveness of Single- Versus Generic Multiple-Tablet Regimens for Treatment of HIV-1 Infection in the United States

Abstract: BackgroundThe possibility of incorporating generics into combination antiretroviral therapy and breaking apart once-daily single-tablet regimens (STRs), may result in less efficacious medications and/or more complex regimens with the expectation of marked monetary savings. A modeling approach that assesses the merits of such policies in terms of lifelong costs and health outcomes using adherence and effectiveness data from real-world U.S. settings.MethodsA comprehensive computer-based microsimulation model was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 52 publications
0
12
0
Order By: Relevance
“…Ten studies were summarized in the previous review [ 11 ]. Three additional studies were identified and are reported in this publication [ 23 , 44 , 45 ]. One study, evaluating overall ART changes in 3850 PLWH, found that modifying therapy resulted in a mean additional cost of €14 (SD €216; range −€528 to +€831) per month per patient [ 44 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Ten studies were summarized in the previous review [ 11 ]. Three additional studies were identified and are reported in this publication [ 23 , 44 , 45 ]. One study, evaluating overall ART changes in 3850 PLWH, found that modifying therapy resulted in a mean additional cost of €14 (SD €216; range −€528 to +€831) per month per patient [ 44 ].…”
Section: Resultsmentioning
confidence: 99%
“…Toxicity and therapy simplifications were cited as the leading causes for regimen changes [ 44 ]. Economic outcomes have been modeled using simulations and insurance claims data including comprehensive computer-based microsimulation to compare the cost-effectiveness of STR to MTR for initial treatment and concluded that the ICER of STR to MTR is $26,383 per quality-adjusted life year [ 45 ]. A multivariate regression model study using Medicaid medical and pharmacy claims data was completed to determine the impact of ART pill burden in 2174 PLWH [ 23 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Approaches to reduce drug costs such as ARV mono or dual therapy are being explored but are not currently widely utilized. The use of generic formulations after patent expiry of proven ARV products has also been extensively discussed . With recent or imminent patent expiry of many core agents used in ART, the greater use of generic ARV drugs has become of immediate relevance to policy makers, plan holders, prescribing physicians and patients; some countries have begun incorporating generics into their HIV health policies in order to reduce costs .…”
Section: Introductionmentioning
confidence: 99%
“… 17 , 18 However, it remains a controversial strategy with conflicting results presented in published cost-effectiveness analysis. 19 , 20 …”
Section: Introductionmentioning
confidence: 99%